Functionalization of reverse osmosis membrane with titania nanotube and polyacrylic acid for enhanced antiscaling properties. Issue 5 (October 2021) - Khoo, Ying Siew; Lau, Woei Jye; Liang, Yong Yeow; Al-Maythalony, Bassem; Ismail, Ahmad Fauzi
Abstract: Membrane surface scaling is a major challenge in reverse osmosis (RO) desalination process that could irreversibly deteriorate the membrane filtration efficiency. In this study, a hydrophilic coating layer was introduced onto the polyamide (PA) layer of self-developed thin film nanocomposite (TFN) membrane via plasma enhanced chemical vapour deposition (PECVD) technique to increase the membrane surface energy barrier and hydrophilicity towards silica heterogeneous nucleation. The results revealed that the acrylic acid-coated TFN membrane (AA-TFN) exhibited excellent resistance against silica scaling after subjected to saturated silica concentration (168 ppm at pH 6.7), with much higher flux recovery rate (FRR) (88%) compared to the uncoated TFN (75.5%) and conventional thin film composite (TFC) (72%) membranes. This is attributed to its enhanced surface hydrophilicity (contact angle of 26°) and better surface charge (zeta potential of −47 mV at pH 6.7) upon the hydrophilic coating layer deposition which retards the scale deposition. The membrane scaling can be further reduced by increasing the feed pH and at the optimized condition (pH 10), the FRR of AA-TFN membrane could reach up to 98.3%, owing to the increased silica solubility at alkaline condition which minimizes the silica aggregation formation on the membrane surface. Our work demonstrated that surface modification of composite membrane using suitable materials and proper feed pH adjustment could offer a great promise in mitigating the scaling for desalination applications. The findings also provide fundamental insights on the importance of membrane surface properties during silica scaling formation. Graphical Abstract: Schematic illustration of scaling mechanism on membrane ga1 Highlights: Rapid and eco-friendly method for surface modification of TFN membrane Silica feed solution at pH 10 can effectively reduce silica aggregation tendency. AA-TFN membrane with higher surface negative charge at pH 10 achieves better FRR (98.3%).